2019
DOI: 10.1589/jpts.31.860
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical reduction of lumbar hyperlordosis, forward sagittal balance and sacral tilt to relieve low back pain by Chiropractic BioPhysics<sup>® </sup>methods: a case report

Abstract: To present the reduction of both lumbar spine hyperlordosis and anterior sagittal balance in a symptomatic patient as treated by Chiropractic BioPhysics ® technique. [Participant and Methods] A 46 year old reported with low back and hip pains for six years. Oswestry disability index scored 28%. Radiographic assessment revealed pronounced anterior sagittal balance with lumbar hyperlordosis. The patient was treated by Chiropractic BioPhysics technique to reverse the spinal deformity subluxation via mirror image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…When applying extension traction protocols, it is important to realize the obvious notion that this applies only to those presenting with hypolordosis, straightening, or kyphosis of the cervical or Lumbar spinal areas, not to those with hyperlordosis. In such cases, different CBP traction protocols apply which are beyond the scope of this brief review [39,56]. Also, in the performance of assessing patient tolerance to extension traction, the slow progression of increasing time and transitioning to a more challenging extension stretch is found in the skill and art of the hands of the practitioner.…”
Section: Contraindications To Extension Tractionmentioning
confidence: 99%
“…When applying extension traction protocols, it is important to realize the obvious notion that this applies only to those presenting with hypolordosis, straightening, or kyphosis of the cervical or Lumbar spinal areas, not to those with hyperlordosis. In such cases, different CBP traction protocols apply which are beyond the scope of this brief review [39,56]. Also, in the performance of assessing patient tolerance to extension traction, the slow progression of increasing time and transitioning to a more challenging extension stretch is found in the skill and art of the hands of the practitioner.…”
Section: Contraindications To Extension Tractionmentioning
confidence: 99%
“…Overall, after 11-months and 57 treatments this patient had a 13.4° reduction in hyperlordosis, a 11.8° reduction of SBA and a 15.4 mm reduction in forward thoracic translation. In comparison, Oakley et al 9) reported on an 8° reduction in hyperlordosis, a 5° reduction in SBA and a 17.4 mm reduction in forward thoracic translation in an adult female after 74 treatments over a 13-month duration. Cardwell et al 10) reported a 6° reduction in hyperlordosis and a 2° reduction in SBA in a 34-year-old male after 33 treatments over 9-months.…”
Section: Discussionmentioning
confidence: 93%
“…Chiropractic BioPhysics ® (CBP ® ) rehabilitation techniques have shown evidence of reducing postural distortions including hyperlordosis of the lumbar spine [9][10][11] . Three case reports demonstrate emerging evidence these methods can nonsurgically reduce lumbar hyperlordosis, thus, more cases are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Additional trends were identified for case management CRs with the highest citation rate since 2015. Musculoskeletal and connective tissue (M00-M99) CRs included an integrative series describing platelet rich plasma injections for sacroiliac joint instability [58], and CRs describing the Chiropractic BioPhysics® methods for posture [59], cervical whiplash [60], and scoliosis [61]. Diseases of the nervous system (G00-G99) CRs described management of postoperative spinal arachnoiditis [62], rehabilitative techniques for a patient with posterior cortical atrophy [63], and integrative management of an incomplete cervical spinal cord injury [64].…”
Section: Icd-10 Trendsmentioning
confidence: 99%